Time lag between the tropopause height and the levels of 7Be concentrations in surface air - Ioannidou, E.; Leppänen, A.-P.; Melas, D.; Ioannidou, A. (HNPS Advances in Nuclear Physics, 2019)
The concentration of 7Be at near surface air has been determined over 2009, which was a year of a deep solar minimum, at three different locations in Finland: Ivalo (68°64’N, 27°57’E), Rovaniemi (66°51’N, 25°68’E) and Kotka (60°48’N, 26°92’E). In geomagnetic latitudes over λ = 60° N, the elevation of tropopause during the warm summer months and the vertical exchange of air masses within the troposphere cause greater mixture of the air masses resulting in higher concentration levels for 7Be in surface air. However, different climatic phenomena, such as air masses from the East, make the correlation between the monthly activity concentrations of 7Be and the tropopause height fairly weak. For Ivalo and Rovaniemi it was found that changes in the daily surface concentrations of 7Be lag the changes in the elevation of the tropopause by four days. In Kotka, the correlation is weakest.